(untitled) (Darya Ganj, New Delhi, 2001)
Contents of material: 1/ Library training. 2/ Library leadership. 3/ Staff training. 4/ Job satisfaction. 5/ Staff organication. 6/ Staff supervision. 7/ Effective librarianship.
Keywords: Library employees,Library personnel management,Librarians; In-service training,In-service training